Human identification using dental DNA in crime scene investigations: from genetic marker analysis to forensic extraction - Turpo-Claudio, Denisse Linda (2025)
The objective of this study was to review the updated literature on the importance of DNA in human identification and on the possibility of extracting DNA from teeth in forensic contexts. The review highlights scientific progress from the development of microscopy to research on the human genome, including the process automation, the analysis of genetic markers, and DNA extraction from teeth. In addition, recent technological advances are discussed and current methods used for DNA-based human identification at crime scenes are described, including Rapid DNA technology, forensic genetic genealogy, forensic DNA phenotyping, and DNA extraction from teeth. In conclusion, DNA-based human identification is fundamental to forensic practice because it supports case resolution and the establishment of kinship relationships. Therefore, staying updated in this field is essential to effectively apply scientific advances to clinical investigations.